Effect of Galactose on β-Galactosidase Synthesis in Escherichia coli K-12 - Llanes, Barbara (1969)
In wild-type strains of Escherichia coli K-12, the rate of thiomethylgalactoside (TMG)-induced β-galactosidase synthesis is decreased in the presence of galactose or glucose. A spontaneous mutant of a K-12 strain, 58-161, which synthesizes β-galactosidase at a low rate was isolated. In this mutant, galactose, after a lag of about one generation time, evoked the same final differential rate of enzyme synthesis as did the gratuitous inducer TMG. However, constitutive, TMG-induced and galactose-induced synthesis in the mutant were subject to inhibition by exogenous glucose. It is concluded that repression of β-galactosidase synthesis derived from glucose is distinct from the inhibition derived from galactose.